Measuring Intellectual Capital in Malaysian Non-Profit Organisation - Siti Zafirah Haiza ABU BAKAR; Amrizah KAMALUDDIN (Communications of International Proceedings, 2020)
Non- Profit Organisation (NPO) is the third sector after the public and private sectors that aims to provide welfare services. The NPO has received an increasing demand for services from the society and community. NPOs are highly depending on the skills and knowledge that are attached to their volunteers and employees. The lack of focus on profit maximization of NPOs and the shift from the non-profit environment to commercialization, pose new challenges to their management. Researchers argued that most of NPO failure is due to ineffective strategy, however these can be solved by using intellectual capital (IC) as their strategic tool.  Previous studies in IC has largely researched on profit organisation leaving the issue of IC and NPO being inadequately explored. Each NPO inherits different characteristics such as different missions, different targets of community, different nature of services and the different ways delivery services. Thus, this study examines measurement of IC from the perspectives of NPO in Malaysia. Questionnaire survey was applied and sixty-seven representatives of NPO in Malaysia participated in this study. Factor analysis was used to identify the themes of IC best suited the NPO.  The analyses resulted in twenty-eight indicators which were further classified into three themes representing the IC. Descriptive statistics were applied to identify the best indicators of IC from Malaysian NPOs perspective. Among the new finding is that IC indicators in NPOs are slightly different from those in the profit organisations.
Keywords: Intellectual capital; Non-Profit Organisation; organisational capital; human capital; relational capital.